Understanding implicit and explicit interface tools to perform visual analytics tasks. - Chang, Remco.; Jeong, Dong Hyun.; Ji, Soo-Yeon.; Greensmith, Tera Marie.; Yu, Byunggu. (Tufts University. Tisch Library., 2017)
Although menu systems are commonly adopted as supporting tools in visualization systems, understanding the effectiveness of supporting tools to perform visual analysis is not broadly studied. In this paper, we performed a study to see the effectiveness of implicit and explicit interface tools-interactive iconic tool (Interactive-Icon) and floating text-based tool (Floating-Menu), respectively. The floating text-based tool is similar to traditional menu systems. The interactive iconic tool is designed as a direct manipulation tool for implicitly selecting objects. To evaluate the use and human performance of both tools, a highly interactive visual anlaytics system is used. With this system, a task-oriented user study is performed. In this study, participants were asked to solve six task questions, three with each tool. All participants' task performances were tracked including accuracy, speed, behaviors and post-task qualitative feedback. From the study, we identified that there is a familiarity effect on the performance of solving the task questions with implicit and explicit interface tools. © 2014 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.